Presence of circulating tumor cells in high-risk early breast cancer during follow-up and prognosis - Trapp, Elisabeth; Schneeweiss, Andreas (Journal of the National Cancer Institute, 2019)
AbstractBackground. The prognostic relevance of circulating tumor cells (CTCs) at the time of primary diagnosis has been well established. However, little info
Published online: October 11, 2018
Gesehen am 14.05.2019